Genetic Diversity Analysis in wild species of Pongamia pinnata (L.) using RAPD and SRAP markers. - Kole, Dr. Pravas Ranjan; Bhat, K V; Chaudhury, Rekha; Malik, S K; Rao, G Rajeshwar (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2015)
Bio -diversityrefers to the variations within the living world while genetic diversity is the sum of genetic characteristics within any species or genus. Genetic diversity serves as a way for populations to adapt to changing environments. With more variation, it is more likely that some individuals in a population will possess variations of alleles that are suited for the environment. Those individuals are more likely to survive to produce offspring bearing that allele. The population will continue for more generations because of the success of these individuals. The extensive literature survey revealed that Pongamia Pinnata L. is an important medicinal plant with diverse pharmacological spectrum. The plant shows the presence of many chemical constituents which are responsible for varied pharmacological and medicinal properties. Furthermore, it also represents a milestone in the field of biofuel industry as one of the most important bio fuel crop. The present investigation was carried out to assess the genetic diversity of 37 wild species of P. pinnata collected from different states from India based on random amplified polymorphic DNA (RAPD) and Sequenced Related Amplified Polymorphism (SRAP) primers. After screening a total of 18 RAPD and 23 SRAP primers were used which gave reproducible amplification banding patterns. In RAPD out of 157 alleles were generated of which 150 were polymorphic across the studied accessions (96.8% polymorphism). For SRAP the total number of amplified products was 145 of which 122 were polymorphic (84.1% polymorphism). The mean polymorphic information content (PIC) for both the markers was 0.77 and 0.68. Variation in combined Jaccardâ€™s coefficient of similarity indicates the high level of genetic variation among the genotypes studied. The overall grouping pattern of clustering corresponds well with the principal component analysis (PCA), confirming patterns of genetic diversity observed among the accessions.Â 